E-Learning and Virtual Simulations for Advancing Maritime Engineering Education - Fernandes, Ruban Baltazar; Rajan, S. S. (Indian Journal of Information Sources and Services, 2025)
The changing needs of the shipping industry call for a more technologically oriented and adaptive model for engineering education. This research discusses integrating e-learning software and virtual simulation tools as cutting-edge means to improve maritime engineering training. The main goal is to assess the efficacy of such technologies in augmenting student involvement, knowledge retention, and practical skill attainment. A mixed-methods design was utilized, linking a recent literature review with case studies and survey data from maritime academies using digital learning environments. The findings of note are that virtual simulations significantly improve students' comprehension of intricate engineering systems and operational practice, particularly while e-learning platforms offer flexibility and accessibility without compromise regarding educational quality. The study also points to difficulties, including technical constraints, upfront costs of implementation, and the requirement for instructor training. The research concludes that while not a complete substitute for experiential learning, simulation and e-learning offer an effective complementary method to traditional maritime training, with far-reaching consequences for affordable, scalable, and standardized training according to international maritime standards.